2008
DOI: 10.1016/j.seppur.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Preparative separation of ketoprofen enantiomers: Choice of mobile phase composition and measurement of competitive adsorption isotherms

Abstract: The present work intends to investigate how mobile phase composition influences the adsorption behavior of ketoprofen enantiomers (a nonsteroidal anti-inflammatory drug) on an amylose-based chiral stationary phase (Chiralpak AD). Three mobile phase compositions were studied: the usual 20% ethanol/80% n-hexane mixture and two pure mobile phases; methanol and ethanol. Pulse and breakthrough experiments under preparative conditions were carried out in order to measure and test adsorption isotherms. The results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
0
22
2
Order By: Relevance
“…Physicians prescribe ketoprofen to individuals suffering with osteoarthritis and rheumatoid arthritis to manage pain and inflammation. There have been several published studies 60,64,65,100,[131][132][133][134][135][136][137][138][139][140][141][142][143] involving the solubility of ketoprofen in organic solvents at 298 K. Most notably, Perlovich et al 136 determined the molefraction solubility of ketoprofen in eight primary alcohols (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, and 1-octanol). Daniels et al 134 later reported the solubility behavior of ketoprofen in ethyl ethanoate, 1,1′-oxybisethane, methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-1-propanol, 1-pentanol, and 1-decanol.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians prescribe ketoprofen to individuals suffering with osteoarthritis and rheumatoid arthritis to manage pain and inflammation. There have been several published studies 60,64,65,100,[131][132][133][134][135][136][137][138][139][140][141][142][143] involving the solubility of ketoprofen in organic solvents at 298 K. Most notably, Perlovich et al 136 determined the molefraction solubility of ketoprofen in eight primary alcohols (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, and 1-octanol). Daniels et al 134 later reported the solubility behavior of ketoprofen in ethyl ethanoate, 1,1′-oxybisethane, methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-1-propanol, 1-pentanol, and 1-decanol.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…Daniels et al 134 later reported the solubility behavior of ketoprofen in ethyl ethanoate, 1,1′-oxybisethane, methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-1-propanol, 1-pentanol, and 1-decanol. Bustamante and Selles, 133 Gantiva and Martínez, 139 Ribeiro et al, 137 and Fini et al 60 also performed ketoprofen solubility measurements at 298 K. Takahashi et al 100 measured the solubility of ketoprofen in diethyl butanedioate, diethyl hexanedioate, diisopropyl hexanedioate, and diethyl decanedioate at 305 K in their study concerning the use of fatty diesters as a means to enhance NSAID permeation through skin. Wenkers and Lippold 64 reported solubility data for ten NSAIDs (aspirin, diclofenac, diflunisal, flufenamic acid, ibuprofen, ketoprofen, nabumetone, naproxen, piroxicam, and tenoxicam) in light mineral oil at 305 K. Kumprakob et al 141 determined the solubility of ketoprofen in binary water + 1,2-propanediol and water + 1,2,3-propanetriol solvent mixtures at 310 K over the entire solvent composition range.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…The gravimetric method for solubility measurements and the adsorption-desorption method used in the experimental determination of binary adsorption isotherms are described in the previous work [1]. In the adsorption-desorption method, the preparative column is saturated with a large amount of feed solution (racemic mixture), with known concentration of both enantiomers, until equilibrium is achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Model equations include the mass balance equations, the equilibrium isotherms models, the initial and the boundary conditions, and can be found in the previous work [1].…”
Section: Simulation Of Fixed Bed and Smb Operation And Performancementioning
confidence: 99%
“…Nonetheless, most of chiral SMB separations can reasonably be processed by a reduced number of these CSPs [218] and thus, reducing what would be a tedious screening work to find the best CSP. Hence, factors like the active species solubility, physical properties of the solvent (mainly its viscosity), and solvent/stationary phase compatibility arise as the main issues when choosing the best combination [219].…”
Section: Search For Suitable Stationary and Mobile Phasesmentioning
confidence: 99%